2020
DOI: 10.1111/jgh.15201
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA LINC00467 acted as an oncogene in esophageal squamous cell carcinoma by accelerating cell proliferation and preventing cell apoptosis via the miR‐485‐5p/DPAGT1 axis

Abstract: Background and Aim Esophageal carcinoma has been regarded as one of the top 10 common malignancies globally. Esophageal squamous cell carcinoma (ESCC) is an important subtype of esophageal carcinoma with approximately 20% survival rate. Long noncoding RNAs were documented to regulate the occurrence or progression of several tumors. However, neither the biological role nor the molecular mechanism of LINC00467 has been explored. This research is aimed to investigating the regulatory mechanism of LINC00467 in ESC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…It has been shown that LINC00467 promotes cell proliferation and migration in liver cancer by binding to IGF2BP3 to enhance the stability of its cis-target genes [22]. In esophageal cancer, LINC00467 can promote esophageal cancer cell proliferation by adsorbing miR-485-5p and reducing the inhibitory effect on the miRNA target gene, DPAGT1 [23]. Previously, our group found that LINC00467 can regulate the phosphorylation of AKT in non-small cell lung cancer by binding to AZGP1 to promote cancer cell migration and invasion [8].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that LINC00467 promotes cell proliferation and migration in liver cancer by binding to IGF2BP3 to enhance the stability of its cis-target genes [22]. In esophageal cancer, LINC00467 can promote esophageal cancer cell proliferation by adsorbing miR-485-5p and reducing the inhibitory effect on the miRNA target gene, DPAGT1 [23]. Previously, our group found that LINC00467 can regulate the phosphorylation of AKT in non-small cell lung cancer by binding to AZGP1 to promote cancer cell migration and invasion [8].…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis of the author indicated that linc00467 can directly regulate the miR-9-5a expression and downstream target peroxisome proliferator activated receptor alpha signaling [ 18 ]. Additionally, a study regarding esophageal carcinoma also found that upregulated linc00467 improved cell proliferation while inhibiting cell apoptosis by regulating the axis of miR-485-5p/dolichyl-phosphate N-acetylglucosaminephosphotransferase 1 [ 27 ]. Research regarding linc00467 outside the digestive system in malignant tumors mainly focused on lung cancer and glioma.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings reveal that LINC00162 functions as a sponge of miR‐485‐5. Several lncRNAs are reported to function as sponge of miR‐485‐5p (Bao et al, 2019; Liu, Yang, et al, 2020; Tu et al, 2019; Wang et al, 2018; Zhang, Hu, et al, 2018). In hepatocellular cell carcinoma, lncRNA DSCR8 activates the Wnt/β‐catenin pathway by decoying FZD7 ‐targeting miR‐485‐5p (Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%